High thermal conductivity of flexible polymer composites due to synergistic effect of multilayer graphene flakes and graphene foam. (June 2016) - Zhao, Yun-Hong; Zhang, Ya-Fei; Bai, Shu-Lin
Abstract: Research on flexible thermal interface materials (TIMs) has shown that the interconnected network of graphene foam (GF) offers effective paths of heat transportation. In this work, a variant amount of multilayer graphene flakes (MGFs) was added into 0.2 vol% GF/polydimethylsiloxane (PDMS) composite. A remarkable synergistic effect between MGF and GF in improving thermal conductivity of polymer composites is achieved. With 2.7 vol% MGFs, the thermal conductivity of MGF/GF/PDMS composite reaches 1.08 W m −1 K −1, which is 80%, 184% and 440% higher than that of 2.7 vol% MGF/PDMS, GF/PDMS composites and pure PDMS, respectively. The MGF/GF/PDMS composite also shows superior thermal stability. The addition of MGFs and GF decreases slightly the elongation at break, but observably increases the Young's modulus and tensile strength of composites compared with pure PDMS. The good performance of MGF/GF/PDMS composite makes it a good TIM for possible application in thermal management of electronics.